Prejudice in "inclusive" spaces: Cisgenderist collusion in the interview context. (May 2022) - Knott-Fayle, Gabriel; Peel, Elizabeth; Witcomb, Gemma L.
Feminist reflexivity aims to (re)consider and challenge power differentials that exist in the research process. This activity is well represented in, for example, research into heterosexism. In this article we expand feminist reflexive practice in relation to cisgenderism through a (re)examination of interview transcripts conducted by a cisgender researcher on the topic of cisgenderism in media representations of trans and intersex sportspeople. Drawing on interviews with 18 cisgender and trans and non-binary participants, we analyse three forms of researcher collusion in cisgenderism, namely: 1) perpetuating cisgenderism in the selection of media materials; 2) assuming trans women are the referent; and 3) disunifying assumptions about trans sportspeople. This reflexive analysis is discussed with regard to how analytical insights can be generated into the operation and functioning of prejudice. In so doing, we further the conception of prejudice as a ubiquitous and latent activity in research practices.